Wavelets: a powerful tool for studying rotation, activity, and pulsation in Kepler and CoRoT stellar light curves - Bravo, J. P. (2014)
Aims. The wavelet transform has been used as a powerful tool for treating several problems in astrophysics. In this work, we show that the time–frequency analysis of stellar light curves using the wavelet transform is a ractical tool for identifying rotation, magnetic activity, and pulsation signatures. We present the wavelet spectral composition and multiscale variations of the time series for four classes of stars: targets dominated by magnetic activity, stars with transiting planets, those with binary transits, and pulsating stars. Methods. We applied the Morlet wavelet (6th order), which offers high time and frequency resolution. By applying the wavelet transform to the signal, we obtain the wavelet local and global power spectra. The first is interpreted as energy distribution of the signal in time–frequency space, and the second is obtained by time integration of the local map. Results. Since the wavelet transform is a useful mathematical tool for nonstationary signals, this technique applied to Kepler and CoRoT light curves allows us to clearly identify particular signatures for different phenomena. In particular, patterns were identified for the temporal evolution of the rotation period and other periodicity due to active regions affecting these light curves. In addition, a beat-pattern signature in the local wavelet map of pulsating stars over the entire time span was also detected.